Acceptance and expectations of healthcare workers and community during the COVID-19 vaccine rollout in Bhavnagar city, western India: a qualitative exploration - Mohit N. Makwana; Hiren J. Shekhda; Mihir P. Rupani (BMC, 2024)
Abstract Background COVID-19 vaccine was launched in India on January 16, 2021. There is a paucity of robust evidence from qualitative studies on the acceptability and expectations of potential recipients from the COVID-19 vaccine around the time of its rollout in India. We conducted this study to explore the acceptance and expectations of the COVID-19 vaccine among the healthcare workers and community in Bhavnagar, India. Methods During January 2021, in-depth interviews were conducted with potential vaccine recipients in Bhavnagar city-health care workers, people over the age of 50, and people of any age with comorbidities. A total of 28 in-depth interviews were performed, including 16 healthcare workers and 12 community beneficiaries. An in-depth interview guide was developed based on the constructs of the health belief model. Following written informed consent from all participants, all interviews were audio-recorded, transcribed in English and codes were generated using thematic analysis. Qualitative qualifiers were used due describe our study findings. Results Most of healthcare workers and a majority of people from the community have shown willingness to be vaccinated with COVID-19 vaccine as they had trust on the results of the clinical trials and on the government. Some participants showed hesitancy, which was attributed to concerns regarding safety and efficacy, negative news reports in the media and lack of awareness regarding benefits of vaccine. Some healthcare workers were hesitant due to a lack of transparency in sharing the results of clinical trials. Very few showed refusal in getting vaccinated due to their belief that they won't be infected with SARS-CoV-2 virus as they might have developed immunity against it. Most of the participants expected good efficacy, minimal/no side effects, rapid and wide coverage of vaccine and a perception of getting back to pre-COVID life sooner. Conclusions Most of the potential recipients were willing to take the COVID-19 vaccine around the time of its initial roll out. Future vaccine rollout campaigns could reduce refusals by timely demand generation activities on vaccine safety/efficacy, involving leaders/influencers, addressing grievances, and minimizing misinformation.